2011
DOI: 10.1371/journal.pone.0028113
|View full text |Cite
|
Sign up to set email alerts
|

Ficolin-2 Levels and FCN2 Haplotypes Influence Hepatitis B Infection Outcome in Vietnamese Patients

Abstract: Human Ficolin-2 (L-ficolins) encoded by FCN2 gene is a soluble serum protein that plays an important role in innate immunity and is mainly expressed in the liver. Ficolin-2 serum levels and FCN2 single nucleotide polymorphisms were associated to several infectious diseases. We initially screened the complete FCN2 gene in 48 healthy individuals of Vietnamese ethnicity. We genotyped a Vietnamese cohort comprising of 423 clinically classified hepatitis B virus patients and 303 controls for functional single nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(27 citation statements)
references
References 31 publications
(43 reference statements)
1
26
0
Order By: Relevance
“…Additionally, our study also showed that there are associations between 258S variant and L-ficolin level in the patients. The association between low L-ficolin levels and the 258S variant has also formerly been observed in other settings: healthy Danish individuals [13], Polish children with recurrent infections [12], Gabonese malaria patients (but not controls) [16], Vietnamese HBV-infected patients and controls [15].…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Additionally, our study also showed that there are associations between 258S variant and L-ficolin level in the patients. The association between low L-ficolin levels and the 258S variant has also formerly been observed in other settings: healthy Danish individuals [13], Polish children with recurrent infections [12], Gabonese malaria patients (but not controls) [16], Vietnamese HBV-infected patients and controls [15].…”
Section: Discussionsupporting
confidence: 59%
“…No significant difference of haplotype distribution was observed between different groups, nevertheless, − 4 A/G heterozygotes was observed to associate with the disease when compared cardiac patients to the controls as well as cardiac to the indeterminate patients. In addition, the AGG promoter haplotype, whose presence is obligatory in − 4 A/G heterozygotes, was also associated with protection against HBV infection in Vietnamese [15], but with susceptibility to schistosomiasis in Nigeria [17]. Our group found the AGA haplotype to be associated with protection against clinical leprosy and rheumatic fever [14], [18], whereas others found it associated with susceptibility to cutaneous leishmaniasis [28].…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…MBL has been described as an acute-phase protein, and the association of MBL with viral hepatitis has been investigated by many groups [24]. However, little was reported about the function of ficolins in viral hepatitis [25,26].…”
Section: Introductionmentioning
confidence: 99%
“…The H-ficolin (H-FCN, FCN-3) gene (FCN3) is a pseudogene in the murine lineage. Accumulating data indicate that each ficolin recognizes an overlapping spectrum of microorganisms (5,6,19,20), and that the deficiency and/or low level of human ficolins has been associated with specific infectious diseases (21)(22)(23).…”
mentioning
confidence: 99%